A four element mm-wave MIMO antenna system with wide-band and high isolation characteristics for 5G applications - Munir, Mehr E.; Kiani, Saad Hassan; Savcı, Hüseyin Şerif; Marey, Mohamed; Khan, Jehanzeb; Mostafa, Hala; Parchin, Naser Ojaroudi (MDPI, 2023)
In this article, we propose a light weight, low profile Multiple Input Multiple Output (MIMO) antenna system for compact 5th Generation (5G) mmwave devices. Using a RO5880 substrate that is incredibly thin, the suggested antenna is made up of circular rings stacked vertically and horizontally on top of one another. The single element antenna board has dimensions of 12 × 12 × 0.254 mm (Formula presented.) while the size of the radiating element is 6 × 2 × 0.254 mm (Formula presented.) (0.56 (Formula presented.) (Formula presented.) × 0.19 (Formula presented.) (Formula presented.) × 0.02 (Formula presented.) (Formula presented.)). The proposed antenna showed dual band characteristics. The first resonance showed a bandwidth of 10 GHz with a starting frequency of 23 GHz to an ending frequency point of 33 GHz followed by a second resonance bandwidth of 3.25 GHz ranging from 37.75 to 41 GHz, respectively. The proposed antenna is transformed into a four element Linear array system with size of 48 × 12 × 0.254 mm (Formula presented.) (4.48 (Formula presented.) (Formula presented.) × 1.12 (Formula presented.) (Formula presented.) × 0.02 (Formula presented.) (Formula presented.)). The isolation levels at both resonance bands were noted to be >20 dB which shows high levels of isolation among radiating elements. The MIMO parameters such as Envelope Correlation Co-efficient (ECC), Mean Effective Gain (MEG) and Diversity Gain (DG) were derived and were found to be in satisfactory limits. The proposed MIMO system model is fabricated and through validation and testing of the prototype, the results were found to be in good agreement with simulations.
Keywords: 28 GHz; 5G; Linear Array; MIMO System; Olympeak